Emotionally Significant Situations Experienced by Physical Education Teachers in Training - Magali Descoeudres , Vincent Hagin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This research aims to identify the types of emotionally significant situations experienced by Physical Education Teachers in Training (PETTs) during the first year of their pedagogical specialization. Furthermore, the valence, the primary emotions, the intensity, the sharing and the effects of each situation is evaluated. Two emotionally significant situations are collected with a narrative questionnaire that 139 PETTs, representing three flights of students (n flight 1 = 45, n flight 2 = 53, n flight 3 = 41) and aged from 25 to 36 years old (n females = 47 and n males = 92) filled out. Data describes 278 experiences treated with an inductive method that described 12 types of situations (six with negative valence, five with positive valence and the type “Student with special needs” has both, positive and negative). Other areas of significance are analyzed with a cross-tabulated tables and descriptive scales method. Negative situations that lead to negative emotions (181/278) were in particular related to the transgression of rules by students and the threat student’s physical integrity. The positive situations (79/278) are linked to motivated students and student’s Learning. Some situations (18/278) are beginning negatively but the issue during the lesson is positive. Most PETTs reported that these situations (233/278) have positively contributed to their professional development. Finally, these results challenge traditional teaching methods and open up the potential value in hybridised coursework model of PETTs, particularly when taking into account the subjective nature of the teaching profession.